2023
DOI: 10.1093/toxsci/kfad014
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor activation affects nitrergic neuronal survival and delays intestinal motility in mice

Abstract: Despite progress describing the effects of persistent organic pollutants (POPs) on the central nervous system, the effect of POPs on enteric nervous system (ENS) function remains underexplored. We studied the effects of 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD), a POP and a potent aryl hydrocarbon receptor (AHR) ligand, on the ENS and intestinal motility in mice. C57Bl/6J mice treated with TCDD (2.4 µg/kg body weight) for eight weeks (once per week) exhibited significant delay in intestinal motility as shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Interestingly, Vijay, A. et al. found that AHR activation affects nitrergic neuronal survival and delays intestinal motility in mice ( Vijay et al., 2023 ). In brief, the AHR plays a regulatory role in intestinal motility, but the relevant mechanisms and studies are still limited and need to be further explored in the future.…”
Section: The Role Of the Aryl Hydrocarbon Receptor In Ibdmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Vijay, A. et al. found that AHR activation affects nitrergic neuronal survival and delays intestinal motility in mice ( Vijay et al., 2023 ). In brief, the AHR plays a regulatory role in intestinal motility, but the relevant mechanisms and studies are still limited and need to be further explored in the future.…”
Section: The Role Of the Aryl Hydrocarbon Receptor In Ibdmentioning
confidence: 99%
“…Recently, Zhizhu decoction has been proven to alleviate slow transit constipation by activating the AHR signaling pathway through gut microbiota (Wen et al, 2023). Interestingly, Vijay, A. et al found that AHR activation affects nitrergic neuronal survival and delays intestinal motility in mice (Vijay et al, 2023). In brief, the AHR plays a regulatory role in intestinal motility, but the relevant mechanisms and studies are still limited and need to be further explored in the future.…”
Section: Ahr In Intestinal Motilitymentioning
confidence: 99%